Systematic Literature Review: Information Technology Transformation within the Muhammadiyah Organization - Sumarhadi, Dedy; Ririh Riswaya, Asep; Fathurohman SW, Oman (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
The development of Information Technology (IT) has brought significant impacts on da'wah patterns, organizational governance, and the management of Muhammadiyah's charitable enterprises (amal usaha). This study aims to conduct a Systematic Literature Review (SLR) of scientific publications on the use of technology within the context of the Muhammadiyah organization, specifically in e-learning, management information systems, digital da'wah, and information governance. The article search was conducted via Google Scholar, Garuda, the Muhammadiyah Aisyiyah Higher Education (PTMA) journal portal, and SINTA-indexed journal databases using the keywords: Muhammadiyah, information technology, e-learning, information systems, and digital da'wah. The inclusion criteria were: (1) scientific journal articles, and (2) a focus on the use of technology within Muhammadiyah's charitable enterprises or organizational structure. From the screening process meeting these criteria, the review results indicate four main themes: (1) the utilization of e-learning in Muhammadiyah schools and higher education institutions, (2) the development of academic and management information systems, (3) the transformation of Muhammadiyah's digital da'wah and communication, and (4) challenges regarding information governance and security. Overall, technology adoption has enhanced the effectiveness of education and da'wah services; however, key weaknesses remain in system integration, data security policies, and IT human resource capacity. Further research is vital regarding data security, centralized information governance, and measuring the impact of digitalization on the development of the Muhammadiyah organization.